1980
DOI: 10.1017/s0007485300007987
|View full text |Cite
|
Sign up to set email alerts
|

Studies of winds and weather during migrations of Simulium damnosum Theobald (Diptera: Simuliidae), the vector of onchocerciasis in West Africa

Abstract: Reports of the presence and absence of biting by Simulium damnosumTheo. in the Volta River Basin in 1962Basin in , 1966Basin in and 1975 were used to identify occasions when sites were invaded by parous and nulliparous females. Circumstantial evidence suggests that this insect is a windborne migrant, and the weather before and during some of these invasions was examined. Although most invasions studied took place south of the Inter-tropical Convergence Zone, for the first time evidence is presented suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…The peaks of infection in May and September could be coincident with the arrival ofinfected migratory insects carried on winds associated with movements of the ITCZ somewhat south of the surface of separation (see Duviard, 1977). The earlier peak in March could be due to arrival on other winds (Magor & Rosenberg, 1980) or due to a species migrating at a different time (Duviard, 1977). Other factors may also be involved such as the decline in insect numbers due to the decreWse in breeding sites at the end of the rainy season, which could affect the reduction in infection late in the year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peaks of infection in May and September could be coincident with the arrival ofinfected migratory insects carried on winds associated with movements of the ITCZ somewhat south of the surface of separation (see Duviard, 1977). The earlier peak in March could be due to arrival on other winds (Magor & Rosenberg, 1980) or due to a species migrating at a different time (Duviard, 1977). Other factors may also be involved such as the decline in insect numbers due to the decreWse in breeding sites at the end of the rainy season, which could affect the reduction in infection late in the year.…”
Section: Discussionmentioning
confidence: 99%
“…Flying insects migrate to achieve dispersal and colonization (Dingle, 1972) by means of persistent, undistracted flights which are aided but not dependent on wind displacement. Apart from large species such as butterflies many small insects are also involved and detailed studies by Duviard (1977) and Magor & Rosenberg (1980) in West Africa have shown migratory activity by cotton stainer bugs (Dysdercus spp.) and by the blackfly Simulium damnosum (Diptera: Simulidae).…”
Section: Discussionmentioning
confidence: 99%
“…Northeast Africa approximately 2,500 -10,000 years before present (Bain, 1981;Keddie et al, 1998;329 Lefoulon et al, 2017;Marshall and Hildebrand, 2002 Simulium spp. subtypes can fly up to 250km (Garms et al, 1982;Post et al, 2013) and up to 500km when 353 aided by favourable wind conditions (Baker et al, 1990;Garms, 1981;Johnson et al, 354 1985;Magor and Rosenberg, 1980). The maximum distances separating our sampling locations along the 355 transect between Mali and Ghana, and between Côte d'Ivoire and Ghana are larger (>500-1000km), and do 356 not align with the long-range vector migration between Côte d'Ivoire and Mali that follow the Southwest-357…”
Section: Genetic Diversity and Demographic History Of O Volvulus 315mentioning
confidence: 99%
“…It was also shown that temperature and other conditions were likely to be important, e.g. air temperatures of 15-20°C at night or 20-40°C by day and flight duration of up to 20 h. The assumptions of wind carriage were also based on the fact that midges have been reported from altitudes of 170 m to 4,000 m above ground level (2,12,13,18,21), as well as on such cases as the reinvasion of Simulium damnosum, carried over 300 km to the Volta River after a control operation (11,22), and capture of Culicoides of the schultzei group on a ship on the East China sea (43).…”
Section: Introductionmentioning
confidence: 99%